Analisi Perhitungan Biaya Per Unit Produk Menggunakan Harga Pokok Produksi (HPP) pada UDMebel Desbo - Githa Aprianingsih (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This research aims to determine the accuracy in determining the cost of production accurately and precisely in the analysis of calculating costs per product unit using the cost of production (HPP) at UD Mebel Desbo. This research uses qualitative descriptive research. This analysis was carried out by calculating the cost of production at the UD company. Desbo Furniture. The data source in the research uses primary data obtained from direct interviews with sources and secondary data obtained from relevant sources. The research informants, namely the key informants are business owners and the main informants are employees. Data collection methods use observation techniques, interview techniques, and documentation techniques. The data analysis technique uses cost of production (HPP). The results of calculating the cost per unit of product based on the cost of goods manufactured (HPP) method produce a cost per unit of malkaln table of Rp. 3,387,250, terals chair of Rp. 2,738,500, and shelf of Rp. 5,449,250. From the 3 products that have been calculated using the cost of production (HPP) method, it can be concluded that determining the unit cost of each product is used as a basic reference for the company in determining the desired selling price.